Biomechanical and clinically controlled study of different fenestration positions in vascularized iliac bone flaps for treating femoral head necrosis - Zeyu Wei; Zeping Lin; Jiale He; Yuxian Chen; You Peng; Zhiyong Li; Yunxiang Lu (Journal of Orthopaedic Surgery and Research)
Abstract Background No appropriate studies have been conducted that compare the biomechanical properties of different fenestration positions in deep circumflex iliac artery (DCIA)-vascularized iliac bone grafts for femoral head necrosis (ONFH) treatment. In this study, we aimed to explore the fenestration locations of DCIA-vascularized iliac grafting in ONFH treatment using FEA and clinical retrospective analysis. Methods We simulated an iliac bone flap transplantation with a vascularized tip by finite element analysis (FEA). Patients were divided into four groups using different femur fenestration positions as follows: center-window group (C-group), superior-window group (S-group), medial-window group (M-group), and inferior-window group (I-group). In this study, we primarily observed the maximum femoral stress at different healing degrees (0, 25, 50, 75, and 100%). We retrospectively analyzed the changes in the postoperative Harris scores (HHS) and the imaging of 16 patients with iliac flaps for ONFH (11 and 5 cases in the center and other-positioned groups, respectively) at the final follow-up visit. Results The FEA results showed that the peak von Mises stresses in the four groups at the time of complete healing were in the following order: group C (20.28 MPa) < group I (20.33 MPa) < group M (20.92 MPa) < group S (22.00 MPa). A clinical retrospective study following a comparison of the two groups found that the mean improvement in HHS was 18.00 ± 12.38 in the center-window group and 13.60 ± 25.55 in the other groups. However, no significant difference was observed in the rate of collapse (36.37 vs. 40.00%) or changes in the HHS between the two groups. Conclusion A fenestration at the center of the femoral neck resulted in improved biomechanical gain and clinical outcomes. Trial registration approval was granted by the Ethics Committee (II202418102).